2023
DOI: 10.1002/cey2.369
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal‐boosted polaron transport in Fe2O3 photoanodes for efficient photoelectrochemical water splitting

Abstract: Introduction of the photothermal effect into transition‐metal oxide photoanodes has been proven to be an effective method to improve the photoelectrochemical (PEC) water‐splitting performance. However, the precise role of the photothermal effect on the PEC performance of photoanodes is still not well understood. Herein, spinel‐structured ZnFe2O4 nanoparticles are deposited on the surface of hematite (Fe2O3), and the ZnFe2O4/Fe2O3 photoanode achieves a high photocurrent density of 3.17 mA cm−2 at 1.23 V versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 56 publications
(97 reference statements)
1
12
0
Order By: Relevance
“…1–5 In this context, developing sustainable energy conversion technologies is of great significance for generating clean energy while reducing or minimizing carbon emissions. 6–9 To date, various emerging electrochemical energy conversion technologies, such as fuel cells and metal–air batteries for clean power generation, water electrolysers for hydrogen evolution, and carbon dioxide (CO 2 ) conversion for hydrocarbon fuel production, etc. , have been widely explored owing to their high energy conversion efficiency and low pollution, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1–5 In this context, developing sustainable energy conversion technologies is of great significance for generating clean energy while reducing or minimizing carbon emissions. 6–9 To date, various emerging electrochemical energy conversion technologies, such as fuel cells and metal–air batteries for clean power generation, water electrolysers for hydrogen evolution, and carbon dioxide (CO 2 ) conversion for hydrocarbon fuel production, etc. , have been widely explored owing to their high energy conversion efficiency and low pollution, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As a highly promising catalyst with low cost and excellent chemical properties, iron oxide is extensively used in catalytic reactions that include water splitting, , H 2 O 2 sensing, , and pollutant degradation. , Inspired by the strategy of oxygen defect engineering for the modulation of catalyst selectivity, an FeO x catalyst with appropriate oxygen vacancy concentrations was synthesized and used for the catalytic H 2 O 2 reduction reaction in this work. Because of the existence of oxygen vacancies in the FeO x catalyst with a moderate amount, the oxygen reduction reaction (ORR) is suppressed, and high selectivity for the H 2 O 2 reduction reaction (HRR) is acquired, as illustrated in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…As a highly promising catalyst with low cost and excellent chemical properties, iron oxide is extensively used in catalytic reactions that include water splitting, 33,34 H 2 O 2 sensing, 35,36 and pollutant degradation. 37,38 Inspired by the strategy of oxygen defect engineering for the modulation of catalyst selectivity, an FeO x catalyst with appropriate oxygen vacancy concentrations was synthesized and used for the catalytic H 2 O 2 reduction reaction in this work.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Significantly, recent investigations have found that the photothermal property of some oxygen evolution catalysts has a positive influence on the oxygen evolution reaction of catalysts and catalyst/semiconductor photoanodes. 15–19 For example, the photothermal effect of cobalt oxide upon near-infrared irradiation can heat the cobalt oxide/BiVO 4 photoanode, which can improve the charge transfer efficiency and water oxidation kinetics. 15 A similar improvement from the photothermal effect was observed on NiCo 2 O 4 /BiVO 4 and ZnFe 2 O 4 /Fe 2 O 3 photoanodes during water oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…15 A similar improvement from the photothermal effect was observed on NiCo 2 O 4 /BiVO 4 and ZnFe 2 O 4 /Fe 2 O 3 photoanodes during water oxidation. 16,17 From the aforementioned reports, it could be speculated that oxygen evolution catalyst/BiVO 4 photoanodes with good photothermal properties may have high water oxidation activity. It is worth noting that most of the oxygen evolution catalysts can only utilize part of solar energy to produce heat.…”
Section: Introductionmentioning
confidence: 99%